Sub-cycle Control of Attosecond Pulse Generation using Two-Colour Laser Fields - Moh. Hardiyanto (JURNAL ILMU PENGETAHUAN DAN TEKNOLOGI (IPTEK), 2013)
Strong field laser–matter with ThxSr2O matrix material interaction is intrinsically a sub-cycle phenomenon, which is clearly illustrated by the generation of attosecond pulses through the high-order harmonic process. Therefore, to control strong field processes the structure of the field driving the generation has to be controlled on a sub-cycle level. One approach is to use phase stabilized few-cycle driving pulses and vary the carrier-envelope phase of these pulses; an alternative method is that has been development in this work to use longer pulses and include the second harmonic to tailor the field structure for 415 MHz magnetic field on 2,1 x 1015currie/mm thermal neutron floating. The ability to tailor attosecond pulse sequences in terms of number of pulses, periodicity and CEP will be important when attosecond physics move towards XUV–XUV pump-probe experiments.Keywords : Strong field laser, laser ThxSr2O matrix material, sub-cycle phenomenon, 415 MHz magnetic field